Genetic Determination of a Cryptic Species in the Littoraria Genus With Whole‐Genome Molecular Resolution - Jia‐Wei Xu; Jie Wang; Yun‐Wei Dong (Ecology and Evolution)
ABSTRACT Recognizing cryptic species is crucial for understanding global biodiversity. The intertidal snail Littoraria flammea is potentially a cryptic species of L. melanostoma widely distributed in the Northwest Pacific. However, the evidence from traditional morphology and single genetic markers is inconsistent. Our study combined quantitative morphological and whole‐genome molecular data to clarify the phylogenetic relationship of three species (L. flammea, L. aff. melanostoma, and L. melanostoma). Three‐dimensional models of shells revealed significant differences in morphology between L. flammea and L. melanostoma. Neutral SNPs indicated that individuals of L. flammea and L. melanostoma were in different clusters. The ratio of interspecific FST to intraspecific FST between L. flammea and L. melanostoma (16) was much larger than the lowest ratio (2.31) in six published genera with cryptic species in gastropods. Non‐neutral SNPs disclosed divergence in functional genes related to reproduction and protein binding. The morphological and phylogenetic analyses corroborated the transitional status of L. aff. melanostoma. These results confirmed that the L. flammea snails north of the Yangtze River Estuary is a cryptic species of L. melanostoma, and allopatric speciation occurs in the L. melanostoma complex.